Study of Fatigue and Bending Properties For Epoxy / Kevlar - Glass Fibers and Hybrid Composite (Baghdad Science Journal, 2025)
In this research a study of the effect of quality, sequential and directional layers for three types of fibers are:(Kevlar fibers-49 woven roving and E- glass fiber woven roving and random) on the fatigue property using epoxy as matrix. The test specimens were prepared by hand lay-up method the epoxy resin used as a matrix type (Quick mast 105) in prepared material composit . Sinusoidal wave which is formed of variable stress amplitudes at 15 Hz cycles was employed in the fatigue test ( 10 mm )and (15mm) value 0f deflection arrival to numbers of cycle failure limit, by rotary bending method by ( S-N) curves this curves has been determined ( life , limit and fatigue strength) of composite . The results show us the reinforcement has important act to increased resistance to the fatigue compared with specimens have non reinforcement this side the specimens reinforcement of glass fiber have resistance to fatigue and fatigue life better than the specimens reinforcement of Kevlar fiber . According to hybrid composite sample fatigue test results showed that the sample which reinforced (Kevlar - regular glass – Kevlar) has a best results which showed stress carrying the most powerful and longer fatigue life with more than (1.3 ×10 6) cycle from other hybrids , while the sample with the sample with three Kevlar reinforced layers have less resistant to fatigue